Predictive Value of First Trimester APRI Score and FIB-4 Index for Gestational Diabetes Mellitus - Kurtoğlu Esen, Şeniz; Kartal Golcük, Esra; Özgen, Gülten; Kender Ertürk, Nergis; Dinçgez, Burcu (The European Research Journal, 2026)
Objective: Inflammation, liver injury, and subclinical fibrotic processes secondary to insulin resistance are thought to play an important role in gestational diabetes mellitus (GDM). This study aimed to evaluate the predictive value of the aspartate aminotransferase–platelet ratio index (APRI) and fibrosis-4 (FIB-4) index, which reflect inflammatory status and hepatic involvement, for the prediction of GDM. Methods: This retrospective study included 3,305 pregnant women who delivered at Department of Obstetrics and Gynecology, Bursa Yüksek İhtisas Training and Research Hospital between January 2020 and December 2024. Of these, 371 women were diagnosed with GDM, while 2,934 women with normal glucose tolerance constituted the control group. Oral glucose tolerance test results, APRI scores, and FIB-4 indices were compared between the groups. Results: The median APRI score and FIB-4 index were significantly higher in the GDM group than in the control group (P<0.001 and P=0.027, respectively). An APRI score >0.22 predicted GDM with a sensitivity of 61.46% and a specificity of 66.02% (AUC=0.667, P<0.001), whereas a first-trimester FIB-4 index >0.53 showed a sensitivity of 66.31% and a specificity of 41.0% (AUC=0.535, P=0.027). ROC analysis demonstrated that first-trimester APRI had significantly greater predictive ability for GDM than FIB-4 (P<0.001). Correlation analysis revealed no significant associations between APRI and clinical parameters, while the FIB-4 score showed weak positive correlations with age and parity. Conclusion: The present study suggests that both APRI score and FIB-4 index may serve as noninvasive biomarkers for the early prediction of GDM. Notably, the APRI score demonstrated superior predictive performance compared with FIB-4 index. Keywords: Gestational Diabetes Mellitus, APRI Score, FIB-4 Index, Inflammation, Oral Glucose Tolerance Test